(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Our main purpose is to introduce the concepts of upper and lower almost contra- (Λ, sp)-continuous multifunctions. Moreover, several characterizations of upper and lower almost contra-(Λ, sp)-continuous multifunctions are investigated